2016
DOI: 10.2485/jhtb.25.427
|View full text |Cite
|
Sign up to set email alerts
|

Study on Suitability of Grafted Bone Following Mandibular Reconstruction Evaluated According to Masticatory Performance Scores Using Half-Portion Gummy Jelly

Abstract: When performing mandibular reconstruction following mandibular segmentectomy, the surgical method that we have been using involves creating a surgical guide plate using a three dimensions model for bending the mandible reconstruction plate. It has been reported that the current method results in an excellent suitability of the graft into the mandible, which allows for a highly esthetic recovery. The purpose of the present study was to evaluate how well the current surgical method enables the grafted bone to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, artificial bone with shape-recovery capacity and high compatibility with the living body has long been needed to solve these problems, and customized artificial bone, in which hard tissues are artificially created based on computed tomography (CT) scans of a patient, has been in development [ 4 , 5 , 6 ]. In particular, titanium (Ti), which has high biocompatibility, has been used in many implantable medical devices in clinical settings, including artificial joints and dental implants, and its high efficacy and safety have been demonstrated [ 7 , 8 , 9 , 10 , 11 , 12 ]. Of the customizable technologies, additive manufacturing (AM) using the selective laser technique, which creates artificial bone with Ti particles based on CT scans of a patient, has attracted attention [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, artificial bone with shape-recovery capacity and high compatibility with the living body has long been needed to solve these problems, and customized artificial bone, in which hard tissues are artificially created based on computed tomography (CT) scans of a patient, has been in development [ 4 , 5 , 6 ]. In particular, titanium (Ti), which has high biocompatibility, has been used in many implantable medical devices in clinical settings, including artificial joints and dental implants, and its high efficacy and safety have been demonstrated [ 7 , 8 , 9 , 10 , 11 , 12 ]. Of the customizable technologies, additive manufacturing (AM) using the selective laser technique, which creates artificial bone with Ti particles based on CT scans of a patient, has attracted attention [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain gummy jelly scores, each subject chewed one test gummy jelly (UHA Mikakuto Co., Ltd., Osaka, Japan) as the chewing sample 30 times, and then spit the comminuted pieces into a gauze cloth. The pieces were transferred to a transparent petri dish and used as samples for visual inspection; two evaluators visually compared the size of the pieces in the same sample on a scale of 1 to 10 in order to obtain the gummy score If the scores of the two evaluators differed, the higher score was used 4,5) . • Tongue pressure: Tongue pressure was measured using a tongue Correspondence to: Dr. Kei Suzuki, Department of Oral Surgery, Osaka Medical College, 2-7 Daigaku-machi, Takatsuki City, Osaka, 569-8686, Japan; Tel: +81-72-683-1221; Fax: +81-72-684-6833; E-mail: ora096@osaka-med.…”
Section: Oral Functionmentioning
confidence: 99%
“…This might be because of their poor mineralization capacity, 9,10 although the fixation between the bone and implant and recovery of occlusal force are also affected by the implant placement site and the size of bone defect. 11,12 Kokubo et al 13 reported that a simple heat treatment at 600 C following a H 2 SO 4 /HCl mixed acid treatment provided Ti with high apatite formation in a simulated body fluid (SBF) 14 that was ion-concentrated so as to be nearly equal to human blood plasma. The treated Ti tightly bonded to living bone when it was implanted into a rabbit tibia.…”
Section: Introductionmentioning
confidence: 99%